Hubungan Pandemik Covid-19 Dengan Beban Kerja Perawat Di Puskesmas Pakisjaya Kabupaten Karawang 2020 - deniati, kiki (STIKes Medistra Indonesia, 2020)
Workload is a condition when workers are faced with tasks that must be completed on time. Understanding the workload and shortages of health workers, especially nurses, is an urgent effort at this time, during the pandemic there was an increase in the number of patients while the current number of nurses was insufficient and caused an excessive workload for the nurses themselves. This research method used a descriptive analytic design with a cross sectional approach. From the results of the Chi-Square statistical test, it was obtained a p value of 0.003, it can be concluded that the p value (0.003) <0.05, this indicates that there is a relationship between the Covid-19 pandemic and the workload of nurses at Pakisjaya Public Health Center, Karawang Regency 2020. The Covid-19 pandemic can affects the workload of nurses at the Pakisjaya Public Health Center, Karawang Regency, when the Covid-19 Pandemic case is high it can increase the workload of nurses to heavy workloads, this heavy ape burden also affects the human resource needs of nurses, if the number of nurses is sufficient, there will be no increase in workload on nurses and nurses can still work productively.